Waterpipe tobacco smoke: Characterization of toxicants and exposure biomarkers in a cross-sectional study of waterpipe employees. (June 2019) - Kaplan, Bekir; Sussan, Thomas; Rule, Ana; Moon, Katherine; Grau-Perez, Maria; Olmedo, Pablo; Chen, Rui; Carkoglu, Asli; Levshin, Vladimir; Wang, Lanqing; Watson, Clifford; Blount, Benjamin; et al.
Abstract: Introduction: Few studies have comprehensively characterized toxic chemicals related to waterpipe use and secondhand waterpipe exposure. This cross-sectional study investigated biomarkers of toxicants associated with waterpipe use and passive waterpipe exposure among employees at waterpipe venues. Method: We collected urine specimens from employees in waterpipe venues from Istanbul, Turkey and Moscow, Russia, and identified waterpipe and cigarette smoking status based on self-report. The final sample included 110 employees. Biomarkers of exposure to sixty chemicals (metals, volatile organic compounds (VOCs), polycyclic aromatic hydrocarbons (PAHs), nicotine, and heterocyclic aromatic amines (HCAAs)) were quantified in the participants' urine. Results: Participants who reported using waterpipe had higher urinary manganese (geometric mean ratio (GMR): 2.42, 95% confidence interval (CI): 1.16, 5.07) than never/former waterpipe or cigarette smokers. Being exposed to more hours of secondhand smoke from waterpipes was associated with higher concentrations of cobalt (GMR: 1.38, 95% CI: 1.10, 1.75). Participants involved in lighting waterpipes had higher urinary cobalt (GMR: 1.43, 95% CI: 1.10, 1.86), cesium (GMR: 1.21, 95% CI: 1.00, 1.48), molybdenum (GMR: 1.45, 95% CI: 1.08, 1.93), 1-hydroxypyrene (GMR: 1.36, 95% CI: 1.03, 1.80), and several VOC metabolites. Conclusion: Waterpipe tobacco users and nonsmoking employees of waterpipe venues had higher urinary concentrations of several toxic metals including manganese and cobalt as well as of VOCs, in a distinct signature compared to cigarette smoke. Employees involved in lighting waterpipes may have higher exposure to multiple toxic chemicals compared to other employees. Highlights: Participants who reported using waterpipes exclusively had significantly higher concentration of urinary manganese compared to never or former smokers. Being exposed to more hours of secondhand smoke from waterpipes was associated with higher urine concentrations of cobalt. Employees involved in lighting waterpipes, compared to those not involved, had higher urine concentrations of cobalt, cesium, molybdenum, 1-hydroxypyrene, acrylamide, acrolein, and 1, 3-butadiene. Waterpipe tobacco users and nonsmoking employees of waterpipe venues had higher urinary concentrations of several toxic metals including manganese and cobalt as well as of volatile organic compounds.